Numerical and experimental study on nonlinear roll damping characteristics of trimaran vessel. (1st March 2022) - Zhang, Yihan; Wang, Ping; Yu, Pengyao; Hu, Jingfeng
Abstract: Roll damping prediction is a complex problem in the field of ship hydrodynamics. For trimaran vessels, there are some issues about the roll damping to be discussed and studied in depth due to multi-hull form. A high-precision prediction method by CFD of roll damping for trimaran vessel is established, and the roll decay motion of multi-forward speeds and multi-degrees of freedom are validated by experiment. The characteristics of linear and nonlinear roll damping are studied by the variation of initial angles and layouts, and the influence of ship forward speed is also analyzed. Due to the strong flow interference and nonlinearity of the emergence of the side hull, an interval section method is proposed to integrate the whole decay curve, so as to calculate the roll damping more accurately. The roll damping components with different layouts and bilge keels are divided by numerical method and verified by empirical formula, and the existence of the flow interference damping has a great influence on nonlinear roll damping. The research on roll damping of trimaran vessel is devoted to improve its roll motion performance, providing reference and help for the research on damping-increasing and anti-rolling methods. Highlights: A complete set of roll damping CFD simulation for a trimaran vessel with experimental validation. Detailed and comprehensive analysis of linear and nonlinear rolling damping of trimaran vessel. Emergence effect analysis of side hull by interval section-based energy method. Analysis of roll damping component for trimaran vessel by numerical method.